The role of professor V. I. Dolotsky in the development of Lliturgics as science and academic subject in Russian higher Church education - Nikolai Karamyshev (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This paper is devoted to one of the key moments in liturgical studies in Russian higher church education. This moment was outwardly marked by the introduction of the new term “liturgics” instead of the old term “church antiquities” in the 1840s. The article shows the role of Professor Dolotsky in the development of liturgics as a science and an academic subject. Based on the analysis of survived manuscript documents, lithoprinted lecture notes and papers, we demonstrate that the introduction of the term “liturgics” at Saint-Petersburg Theological Academy in 1849–1853 and its following adoption in higher church education took place with a direct involvement of V. I. Dolotsky. Employing historical approach, Dolotsky signifi cantly broadened the content of his course of lectures, supplementing it with historical data. Dolotsky’s scholarly interests can be identifi ed on the basis of his articles, academic course programmes and lithoprinted lecture notes. They were related, above all, to text analysis of variable parts of church service, particularly holiday service. Besides, Dolotsky expressed interest in the origin of Holy days and their orders in antiquity. Here, by means of the historical approach, Dolotsky made use of the evidence of ancient Holy Fathers and emphasised the importance of employing liturgical sources of heterodox confessions that had common origins with the Orthodox Church. Thus, Dolotsky came to be the first Russian scholar of liturgics and provided a foundation for the further development of historical liturgics in Russian theological science.